Pengaruh keadilan organisasi, kepuasan kerja, komitmen organisasi dan prestasi tugas terhadap tingkah laku kewargaan organisasi dalam kalangan pensyarah - Muhamad Ariff Ibrahim,; Wan Shahrazad Wan Sulaiman,; Noor Izzaty Ibrahim,; Mohd Ahsani Abdul Malek,; Azman Bausing, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Organizational citizenship behavior is a part of job performance components and influences organization effectiveness. This study aims to examine the relationship between organizational justice, job satisfaction, organizational commitment, task performance and organizational citizenship behavior among academicians. In addition, this study aims to examine the role of organizational justice, job satisfaction, organizational commitment and task performance as predictors towards organizational citizenship behavior among academicians in a higher learning institution. A total of 211 respondents participated in this study. Five instruments were used, namely Organizational Justice Questionnaire, Minnesota Satisfaction Questionnaire (MSQ), Organizational Commitment Questionnaire (OCQ), Organizational Citizenship Behavior scale and Task Performance scale developed by the researchers. Results showed that there was a significant correlation between organizational justice, job satisfaction, organizational commitment, task performance and organizational citizenship behavior. Results of multiple regression showed that organizational commitment and task performance significantly predicted organizational citizenship behavior among academicians. The study also found that organizational citizenship behavior was not predicted by organizational justice and job satisfaction.